Solved, for All Practical Purposes. - Ledgard, Henry; Vardi, Moshe Y.; Moran, Tom; Ben-Ari, Mordechai; Byrd, David (Communications of the ACM, 2011)
Letters to the editor are presented in response to three articles from the July 2011 issue: “Solving the Unsolvable” by Moshe Y. Vardi in the July 2011 issue, “Non-Myths About Programming” by Mordechai Ben-Ari, and “Cellular Telephony and the Question of Privacy” by Stephen B. Wicker, together with responses by the authors to the first two.